An algorithm of the rank of a dependent fuzzy set. (17th November 2017) - Li, Yonghong; Shi, Yingjie; Liu, Yanbing; Zhang, Qinghua; Qiu, Dong; Duan, Huiming; Li, Jiang
Abstract: The rank of a dependent fuzzy set in a closed fuzzy matroid is discussed and several useful results for the rank of a dependent fuzzy set are given in this paper. Based on these theorems, an algorithm of obtaining the rank of a dependent fuzzy set is presented.